Optical and Radiative Properties of Aerosols over Two Locations in the North-West Part of India during Premonsoon Season - Yogesh Kant; Atinderpal Singh; Debashis Mitra; Darshan Singh; P. Srikanth; A. S. Madhusudanacharyulu; Y. N. V. Krishna Murthy (Advances in Meteorology)
The present study examines the aerosol characteristics over two locations in the northwest region of India (Dehradun and Patiala) during premonsoon season of 2013. The average mass concentrations of particulates (PM10; PM2.5; PM1) were found to be 118±36, 34±11, and 19±10 µgm−3 and 140±48, 30±13, and 14±06 µgm−3 over Dehradun and Patiala, respectively. The average aerosol optical depth (AOD500 nm) is observed to be 0.62±0.11 over Dehradun and 0.56±0.21 over Patiala. Ångström exponent and fine mode fraction show higher values over Dehradun as compared to Patiala. The average mass concentration of black carbon was found to be 3343±546 ngm−3 and 6335±760 ngm−3 over Dehradun and Patiala, respectively. The diurnal pattern of BC is mainly controlled by boundary layer dynamics and local anthropogenic activities over both the stations. The average single scattering albedo (SSA500 nm) exhibited low value over Patiala (0.83±0.01) in comparison to Dehradun (0.90±0.01), suggesting the abundance of absorbing type aerosols over Patiala. The average atmospheric aerosol radiative forcing is +37.34 Wm−2 and +54.81 Wm−2 over Dehradun and Patiala, respectively, leading to atmospheric heating rate of 1.0 K day−1 over Dehradun and 1.5 K day−1 over Patiala.